Theological Comments mentioned in Jâmi’al- Tirmdzî and Its Application in Achieving Acceptance and Understanding within Muslim Community - Fouly, Nabil (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This is a study of the theological comments of Imam Tirmidzi and those of which he mentioned in his book “al-Jâmi’ al-Kabîr”. These comments provide us a picture of how the early generations of Islam dealt with the issues related to Creed and Aqêda, Furthermore the issue of scarcity of views and comments associated to the early generations of Islam in dealing the issues of Creed and Aqêda is also dealt with in this study. Most of the comments of at-Tirmidzi in the study are mentioned as exact quotations and then they are classified according to the topics they are related to, and after classification analysis of the content along with the methodology and inclination of the holder of the opinion regarding these issues of Aqêda is studied. The study shows that the issue which overwhelmed and kept the early generation of Islam occupied was the issue of amal (Actions) related to those issues of creed or in other words they were more interested in the actions which has to exist as a result of that aqeedah hence those whose thoughts and emotions are attached to these early generations of Islam have to follow them in their pursuit of actions more than any other thing. Moreover regarding the conception of anthropomorphistic attributes the study yields that the more accurate and sound opinion associated to the early generations in this regard in the opinion of Tafwêdhi.e to depute the knowledge of its meaning to God alone and that on extremely rare occasions they use to incline towards their taweel i.e metaphorical interpretation. And this last issue in particular must and should be discussed within scholarly circles only and the general public should refrain from indulging themselves in such technical issues.